Establishment of Typical Operating Conditions for Train Traction System Based on Short Trip Analysis Method - LU Xiulong; GUO Yidan; CHENG Hao; DENG Ming; ZOU Xiaoyang (Kongzhi Yu Xinxi Jishu)
This paper presents a method to establish typical operating conditions for train traction systems by combining site-based short trip analysis with nonparametric tests, in order to overcome various obstacles, such as inadequate efficiency testing results based on rated points of train traction systems, which often fail to accurately reflect the actual energy efficiency level of systems during long-distance operation under multiple conditions, and the existing absence of typical operating conditions essential for supporting the evaluation of traction systems' energy efficiency levels and guiding the energy-saving design of products. First, short trips were categorized, screened and randomly combined. Then, the optimal short-trip combination was identified through nonparametric tests. Subsequently, the typical operating conditions were developed, taking the traction system of an electric locomotive model as a case study. Furthermore, the proposed method was verified by analyzing errors in operating characteristic parameters and assessing the similarities in velocity-force (V-F) distribution probability two-dimensional matrix. The verification results revealed a deviation between the constructed typical operating conditions and the characteristic values derived from sampled data at 4.54%, and the consistency in V-F distribution probabilities at 98.06%. These findings indicate that the method proposed in this paper accurately reflects the actual operating characteristics of train traction systems, with the established typical operating conditions closely aligning with the actual operating conditions of train traction systems, underscoring their potential for aiding in energy-saving design and energy efficiency evaluation for train traction systems.